Nov 2, 2019

12 LAWS AND RULE OF BOOLEAN ALGEBRA

12 rules and laws boolean algera
basic rules of boolean algebra

BOOLEAN ALGEBRA'S RULES AND LAWS:

  A English mathematician, philosopher and logician George Boole 1854 given a mathematical theories and few logical algebra named as Boolean Algebra..which consist of 12 laws or rule which briefly described Boolean Algebra which are:
            
1.    A + 0 = A
2.    A + 1 = 1
3.    A . 0  = 0
4.    A . 1  = A
5.    A + A = A
6.    A + Ā = 1
7.    A . A = A
8.    A . Ā= 0
9.    (A) = A
10. A + A B = A
11. A + ĀB = A + B
12. (A + B)(A + C) = A + BC

Derivation of Laws Using Gates And Truth Table:


RULE # 1 (  A + 0 = A) 

boolean simplification rules
A + 0 = A

A
0
  A+0
0
0
0
1
0
1

RULE # 2 (A + 1 = 1)

basic rules of boolean algebra
A + 1 = 1







A
1
  A+1
0
1
1
1
1
1

RULE # 3 (  A . 0  = 0)

boolean algebra rules pdf
A .0 =0






A
0
  A . 0
0
0
0
1
0
0

RULE# 4 (A . 1  = A)

logic algebra rules
A. 1= A







A
1
  A . 0
0
1
A
1
1
A

RULE #5 ( A + A = A)

12 rules of boolean algebra
A + A = A.







A
A
  A +A
0
0
A
1
1
A


RULE # 6(A + Ā = 1)


logic gates simplification rules
A + Ā = 1








A

Ā

 A+ Ā=1
0
1
1
1
0
1

RULE # 7(A . A = A)

boolean algebra laws and rules pdf
A.A=A






A
A
  A .A
0
0
A
1
1
A

RULE # 8 (  A . Ā= 0)

logic gate simplification rules
A . Ā= 0






A

Ā

 A . Ā
0
1
0
1
0
0

RULE # 9 ((A) = A)

boolean expression simplification rules
A Double not = A







RULE #10 ( A + A B = A)

= A+ AB
= A (1 + B)
= A (1)             (from rule no 2 A + 1= 1, replace the variable A by B so  B+1 or 1+B=1)
= A
boolean algebra laws and rules
A + AB = A








RULE # 11( A + ĀB = A + B)

= A + ĀB
= A + AB + ĀB   (from rule no 10,A+AB=A)
= A + B(A +Ā )
= A + B(1)          (from rule no 6, A +Ā = 1)
= A + B              (which is equal to right hand side)

algebra laws and rules
 A + ĀB = A + B








RULE#12(. (A + B)(A + C) = A + BC)

= (A + B)(A + C)
= AA + AC + AB + BC
= A + AC + AB + BC        (from rule no 7 A.A = A)
= A(1 + C) + AB + BC
= A (1) + AB +BC             (from rule no 2, 1+C=1)
= A + AB + BC
= A + BC                           (from rule no 10 , A + AB = A) hence it is equal to right hand side
boolean equation rules
(A+B)(A+C)=A+AB











                                           physics label                                                                                                  

0 comments:

Post a Comment

Please do not enter any spam link in the comment box